Leverage, Sales Growth and Profit Management: Does Corporate Governance Matter? - Fauji Sanusi; Annisa Annisa; Enok Nurhayati; Yeni Januarsi (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to investigate (1) The Effect of Leverage on Profit management; and (2) The Effect of Sales Growth on Profit management. (3) The effect of leverage on profit management with good corporate governance as a moderating variable; (4) The influence of sales growth on profit management with good corporate governance as a moderating variable. This study focused on consumer goods businesses listed on the Indonesia Stock Exchange between 2016 and 2020. Purposive sampling is employed as the sampling method, with 26 companies serving as the research sample. The panel data regression model with the Common Effect Model (CEM) approach is used in this study for hypothesis testing, and the Moderated Regression Analysis (MRA) model is used for evaluating the moderating variable. The EViews application version 12 is used to analyze the data from both models. The findings indicate that leverage has a strong favorable impact on profit management. While Sales Growth has no discernible impact on Profit management. Meanwhile, while good corporate governance can moderate the impact of leverage on profit management, good corporate governance cannot moderate the impact of sales growth on profit management. This study includes corporate governance variable as this inclusion become originality from currepaper. The implication is of this study is firm’s debt structure and the quality of firm’s governance play essential contribution on how management create better performance.